2022
DOI: 10.1001/jamanetworkopen.2022.43127
|View full text |Cite
|
Sign up to set email alerts
|

Return on Investment of the COVID-19 Vaccination Campaign in New York City

Abstract: ImportanceNew York City, an early epicenter of the pandemic, invested heavily in its COVID-19 vaccination campaign to mitigate the burden of disease outbreaks. Understanding the return on investment (ROI) of this campaign would provide insights into vaccination programs to curb future COVID-19 outbreaks.ObjectiveTo estimate the ROI of the New York City COVID-19 vaccination campaign by estimating the tangible direct and indirect costs from a societal perspective.Design, Setting, and ParticipantsThis decision an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…Vaccines have a well-established record of being safe, reliable and highly cost-effective public health interventions with proven capacity to reduce preventable deaths, defer healthcare costs, and prevent long-term disabilities associated with infectious diseases ((VoICE), 2019 ; Kirson et al, 2022 ). Data have emerged from across multiple jurisdictions globally to show that vaccination against SARS-CoV-2 had clear patient, health system, and immediate and long-term societal benefits (Kelly et al, 2022 ; Kirson et al, 2022 ; Lopez et al, 2021 ; Marcellusi et al, 2022 ; Sah et al, 2022 ). Our study corroborates these findings and strongly asserts how vaccination against SARS-CoV-2 represents a priority population health intervention to pre-emptively mitigate predicted strain on health systems.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccines have a well-established record of being safe, reliable and highly cost-effective public health interventions with proven capacity to reduce preventable deaths, defer healthcare costs, and prevent long-term disabilities associated with infectious diseases ((VoICE), 2019 ; Kirson et al, 2022 ). Data have emerged from across multiple jurisdictions globally to show that vaccination against SARS-CoV-2 had clear patient, health system, and immediate and long-term societal benefits (Kelly et al, 2022 ; Kirson et al, 2022 ; Lopez et al, 2021 ; Marcellusi et al, 2022 ; Sah et al, 2022 ). Our study corroborates these findings and strongly asserts how vaccination against SARS-CoV-2 represents a priority population health intervention to pre-emptively mitigate predicted strain on health systems.…”
Section: Discussionmentioning
confidence: 99%
“…33 Achieving high booster uptake requires investment and outreach at the national level. Despite direct costs associated with vaccination (eg, vaccination clinic setup, vaccine storage and transportation, vaccine administration, vaccine doses, and vaccine waste) and those incurred indirectly as a result of work days lost due to vaccination clinic visits or adverse reactions to vaccines, the return on this investment could be substantial, 34 with potential reductions in severe outcomes and school absenteeism.…”
Section: Discussionmentioning
confidence: 99%
“…Direct costs included medical costs due to COVID-19 cases, comprising outpatient care and hospitalization for acute COVID-19 and treatment of PCC. Vaccination program costs encompassed the cost of purchasing and administering COVID-19 vaccines, including estimated wastage, as well costs associated with delivery of the program to the population, such as storage and transportation, clinic set up, and advertisement and outreach (( 10 )). The cost of wasted doses excluded vaccine administration costs.…”
Section: Methodsmentioning
confidence: 99%
“…Initial economic evaluations of COVID-19 vaccination in North America have demonstrated that COVID-19 vaccination programs have resulted in substantial economic benefit (( 10 , 11 )). An analysis of Canada’s vaccination program estimated a net cost-benefit of −$0.4 billion to $2.1 billion when considering treatment costs and lost productivity due to illness, and a further $27.6 billion benefit due to prevented mortality (( 11 )).…”
Section: Introductionmentioning
confidence: 99%